Evaluation of the Cytotoxic Effects of CAM Therapies: An In Vitro Study in Normal Kidney Cell Lines. (3rd February 2014) - Arora, Shagun; Tandon, Chanderdeep; Tandon, Simran
Abstract : The purpose of this current study was to justify the incorporation of complementary and alternate medicine (CAM) in current cancer treatments. The major drawback of anticancer drugs is their nonselective killing, which ultimately leads to attrition of normal cells. Keeping this as the foundation of our study, we made an effort to compare the cytotoxicity associated with a known chemotherapeutic drug 5-Fluorouracil (5-FU), with certain CAM therapies previously reported to have anticancer activity. The parameters chosen for the study were based on antiproliferative and cytotoxic effects on normal, kidney epithelial cells (NRK-52E). The MTT assay, colony formation assay, DNA fragmentation, and differential staining using AO/EB, following treatment with either 5-FU or CAM therapies, were performed. The CAM therapies under study were various extracts of wheatgrass, roots of Achyranthes aspera (AA), mushroom extracts ( Pleurotus ostreatus, Macrolepiota procera, and Auricularia polytricha ), and a homeopathic drug, Ruta graveolens (Ruta). The results showed that treatment of normal cells with the CAM therapies led to minimum cell damage in comparison to 5-FU. This evidence-based study will lead to greater acceptance of alternative therapies against cancer.